Odškodninska odgovornost za uporabo umetne inteligence v delovnem razmerju - Weingerl, Petra (Delavci in delodajalci, 2023)
The paper discusses liability for damages caused by the use of artificial intelligence systems within the scope of the employment relati- onship. For this purpose, the Slovenian regulation of liability of the emplo- yee and the employer will first be presented. This will be followed by a presentation of specific risks for the occurrence of damage in the use of artificial intelligence in employment relationships and the legal rules for liability if these risks materialize. The paper concludes with a discussion of the novelties proposed at the EU level.
Keywords: algorithmic discrimination; artificial intelligence; civil liability; delovna razmerja; delovno pravo; odškodninska odgovornost; personal data protection; umetna inteligenca; varstvo osebnih podatkov; workplace